Sticherus salinoi, a New Species of Sticherus (Gleicheniaceae, Polypodiopsida) from Brazil - Lima, Lucas Vieira; Salino, Alexandre (Phytotaxa, 2018)
Sticherus salinoi, a new species of Gleicheniaceae from Brazil, is here described, illustrated, and compared to its most similar species. An identification key to the Neotropical species of Sticherus with glabrous segments is also presented.